Forest fire resource planning with integer programming: an application in Turkey - Tezcan, Burcu; Eren, Tamer (Forest science and technology, 2025)
Forest fires are among the serious disasters that cause disruption of ecological balance, economic losses and threats to life safety. In order to effectively combat such disasters, strategic planning of firefighting equipment is of great importance. In this context, this study develops an optimal resource planning model for forest fire response using integer linear programming method. The model aims to make the most appropriate equipment allocation by considering parameters such as fire spread rate, fire priority level, number of equipment, and response time. In this context, 99 first response vehicles, 54 land vehicles, 18 water supply vehicles, and 2 helicopters used in fire fighting in the Edremit district of Balıkesir were included in the model. Each type of equipment is evaluated according to its operational capacity and mobility, and resource allocation is optimized accordingly. Within the scope of the application based on real-life data, the planning and allocation of firefighting equipment in Edremit district, one of the riskiest regions of Balıkesir province in terms of forest fires, has been optimized over four scenarios representing different fire conditions. The objective function aims to minimize the total transportation time and the model results show that the equipment reaches the fire points in the shortest time. The findings show that the proposed model can speed up the firefighting process and increase efficiency in resource utilization. It is thought that this study can guide decision makers in the fight against forest fires.